ANALYSIS OF CORPORATE SUSTAINABILITY PRACTICE AND IMPACTS TO CORPORATE VALUES IN MALAYSIA: DATA VISUALIZATION APPROACH - Christopher Jerry Thomas; Jasman Tuyon; Hylmee Matahir; Samir Dixit (International Journal of Accounting, Finance and Business, 2020)
In response to the United Nations sustainable development goals agenda, companies uses sustainability reporting as a tool to meet stakeholders’ expectation and promoting accountability which are essential for achieving sustainable competitive advantage and creating corporate values through sustainability. In recent years, there is a growing body of sustainability practice and reporting globally, but the nature and extent in Malaysia have not been sufficiently explored leaving the impacts of sustainability practice to corporate values remain puzzle. This study aims to provide a comprehensive analysis of corporate sustainability practice of FTSE4Good Bursa Malaysia index components through the following analysis. First, review of corporate sustainability policy development. Second, analyse corporate sustainability reporting practice by public listed companies using data visualization tools that provide an accessible way to see and understand trends, outliers, and patterns based of ESG scores in relations to firm financial performance proxies. This research would provide insights into this new sustainable corporate finance practice, yet very promising in enhancing firm values, therefore, have important implications for corporate and portfolio managers.